The significance of fitness camps for developing and integrating sport tourism - Jajić Jelena; Tišma Stefan; Perić Dušan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
During the develomental stages, tourism acqured new forms, to meet increasingly stringent criteria of tourism consumers. The tourism market, enriching the ofer, changingthe metod and content of vacation, outsade of housing. The basis of modern tourism is a comprehensive offer of selective forms of tourism, as a step towards meeting the requirements and needs of a demanding tourist consumers, of the twenty-first century. While in the past the sport was associated with tourism and travel in a variety of sports events, in modern, sports tourism has a much broader role. Today, the relationship of sport and tourism industry is considered, which is the consequence of sports tourism that is designed by considering the sport as a touristic attraction, or by highlighting and defining the quality of sport, which together represent a unique contribution to the tourism industry. From the aspect of sports tourism, fitness is an essential component for tourism, improving health, getting fit and improving relations between people. Fitness can be a major motivation for consuming commitment to appropriate tourism product. A possible idea could be the presentation of fitness boot camps, especially those that are performed in the open air, because it does not require additional, large, tangible assets, and provide the opportunity for existing recreational facilities, with minimal refreshments. One of the possibilities of progress fitness camps as a form of sport tourism is their involvement in other forms of tourism.